Unlocking Africa’s Bamboo Value Chain for Sustainable Development (International Journal of Bamboo and Rattan, 2023)
Bamboo currently grows almost everywhere on Earth. It falls under the category of grass and holds the title forbeing the fastest-growing plant with recorded growth rates of up to 1m/day for some species. It is one of the most versatile plant species possessing both the strength of hardwood and the sustainability of grass. It thrives and grows in a diverse range of climates. Its ancient origin is believed to be China and there are about one thousand five hundred known species.African countries can unlock the full potential of the bamboo value chain, leading to economic growth, job creation, environmental sustainability, and the empowerment of local communities. To fully benefit from the bamboo boom, the private sector needs to be at the heart of green economy development in order to drive demand and provide investment. Value addition needs to be more innovative if African bamboo is to take the global market by storm.
Keywords: sustainability; Development; Bamboo Value Chain